Verbesserung der Prozesskette zur Herstellung mikrostrukturierter Linsen für automobile Scheinwerfer - Zimmermann, Dennis (Spektrum der Lichttechnik, 2021)
This work deals with the design, fabrication and quality control of microstructured lenses for headlamp projection systems. An algorithm is described to structure smooth lens surfaces. The data transfer for manufacturing steel tools for the injection molding process is explained. A reverse engineering process used to qualify the tools is presented.